Pengaruh Penggunaan Pop-Up Book Terhadap Kecerdasan Verbal-Linguistik Anak Usia 5-6 Tahun Di TK Swasta Excellent Aceh Singkil T.A 2023/2024 - Imel Fauziah Hasya; Anita Yus (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research aims to determine whether there is an influence from the use of popup books on children's verbal-linguistic intelligence in the Aceh Singkil Excellent Private Kindergarten. This research uses experimental research using a quantitative approach. The research method used in this research is Quasi Experimental Design with the Equivalent Time Sample Design. The sample in this study was 18 children, sampling was carried out using a simple random sampling technique. The data analysis technique used in this research is non-parametric hypothesis testing by tabulating data, calculating average values, and interpreting the data. The findings of this research show that there is a significant influence from the use of pop-up book media on the verbal-linguistic intelligence of children aged 5-6 years in the Aceh Singkil Excellent Private Kindergarten for the 2023/2024 academic year. From these findings, it can be seen that the research results obtained show that there is an increase that occurred from treatment 1 to treatment 2, where the real level α = 0.000.